Analisis Hubungan Pola Menstruasi dan Pengetahuan Remaja Terhadap Kejadian Anemia pada Remaja Putri di SMA Darut Taqwa Purwosari Tahun 2024 - Sari, Cindy Clara; Tabita Hasianna Silitonga, Hanna; Lewi Santoso, Jemima; Ritunga, Imelda; Charles Pardomuan Tua Siahaan, Salmon (Bahasa Indonesia, 2025)
Anemia is a significant public health issue in Indonesia, particularly iron deficiency anemia, which has a relatively high prevalence among adolescent girls. Various factors can contribute to this condition, one of which is an irregular menstrual cycle. A deeper understanding of the contributing factors of anemia is essential for adolescent girls in order to prevent this condition. The aim of this study was to determine the correlation between menstrual patterns (frequency, cycle, and duration) and the occurrence of anemia. This research employed a quantitative analytic observational design with a cross-sectional approach. The study was conducted at SMA Darut Taqwa Purwosari. The sample size was determined using the Slovin formula and a simple random sampling technique, resulting in 253 female students as participants. Data collection was performed using the Fora 6 Plus device to measure hemoglobin levels, and a questionnaire to assess the respondents’ menstrual cycles. Data analyses were processed using SPSS software with the Chi-square test. The results showed that 39.1% of students experienced anemia, 32.8% had increased menstrual volume, 38.7% had prolonged menstrual cycles, and 48.2% had extended menstrual duration. The Chi-square test revealed a significant relationship between menstrual patterns (volume, cycle, and duration) and the incidence of anemia with a p-value < 0.001. The study concludes that there is a significant correlation between menstrual patterns and the occurrence of anemia among adolescent girls at the study site.